Visualization of surface transformations during laser ablation of solids by femtosecond pump–probe time-resolved microscopy - Carrasco Garcia, Irene M.; Vadillo-Pérez, José Miguel; Laserna-Vázquez, José Javier (Elsevier, 2015)
A femtosecond time-resolved microscope (fs-TRM) based on pump–probe excitation has been used to follow the dynamic of the processes occurring during laser–matter interaction, from initial surface alterations to final solidification through transient melting. The time-resolved microscope described in the manuscript has been designed to allow a precise control of the excitation beam to cover ranges below and above the plasma formation energy, and a large temporal variation in the pump–probe delay to include the different timescales of the different processes occurring up to the plasma formation. The microscope has been demonstrated to be robust and allows the subpicosecond monitoring of laser ablation single-shot events, of importance in the analysis of ultra thin layers, or biological tissues. The fs-TRM excites (pump) the sample with 35-fs laser pulses at 800 nm and follows the processes by a second (probe) beam at 400 nm. The relative delay between both beams allows the acquisition of pictures with a temporal resolution of 200 fs up to 3 ns after the reaching of the pump pulse. In the ablative regime near the ablation threshold, transient surface reflectivity patterns (dynamic Newton fringes) are observed from a ps to ns time-scale. The timescale and number of such rings are affected by the fluence value. Significant differences between metals (Al, Cu and Sn), semiconductors (Si) and polymers (polytetrafluoroethylene and polyurethane) have been also observed in the transformation patterns.
Keywords: Ablación láser; Láseres de femtosegundo; Superficies (Tecnología) -- Análisis; Femtosecond laser ablation; Pump-probe; Time-resolved microscopy; Ablation dynamics; Laser-matter interaction